Incidence and Anatomical Properties of Retromolar Canal in an Iranian Population: A Cone-Beam Computed Tomography Study - N. Nikkerdar; A. Golshah; M. Norouzi; S. Falah-Kooshki (International Journal of Dentistry)
Objectives. Retromolar canal (RC) is an anatomic structure, and due to increasing demand for surgical procedure in the retromolar area of the mandible, the identification of the retromolar canal has become an issue of clinical concern. It can innervate the third molar and some of the muscles around the posterior segment of the mandible, complicating surgical procedures in the retromolar area and root canal treatment of third molars. The aim of this study was to evaluate the incidence and anatomical properties of RC in a western Iranian population using cone-beam computed tomography (CBCT) images. Materials and Methods. Two hundred bilateral CBCT images were collected and screened in the three spatial planes for the presence of an RC. Anatomical properties and location of the RCs were assessed according to their course and distance from the surrounding structures. The relationship between the presence of RC and age, sex, side, and presence of second and third molars was also evaluated. Independent samples t-test, ANOVA, Tukey’s post hoc test, paired t-test, and chi-square were used to compare groups. Results. At least one RC was observed in 22% of the mandibles. Its bilateral incidence was 5.5%. Two major types of canals were detected, namely, type I, following a straight or curved course from the mandibular canal (MC) to the retromolar area (47.3%), and type II, coursing from the retromolar area to the radicular part of the third molar (52.7%). Regarding linear measurements, the mean RC diameter and the mean distance to the MC, second, and third molars were 0.68 ± 0.31, 13.7 ± 2.8, 15.3 ± 3.0, and 7.3 ± 2.3 mm, respectively. Conclusion. Based on the results of this study, RC was found in 22% of the cases; thus, it should be considered as a normal anatomical variation in the Iranian population rather than a rare finding.